Ethnographic Narratives as World Literature Uneven Entanglements in European and South Asian Writing - De Capitani, Lucio (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Lucio De Capitani's book offers a refreshingly original take on the current debates in postcolonial studies and world literature through the crucial anchor of literary ethnography. In three geographically ambitious and tightly structured chapters, De Capitani insightfully argues that colonial and postcolonial literary works have either tacitly endorsed or militantly critiqued the colonial-anthropological means of knowing self, society, and the world." -Sourit Bhattacharya, Lecturer in Global Anglophone literatures, University of Edinburgh, UK "This thought-provoking exploration of the relationship between anthropology and literature offers a fresh approach to the field of world literary studies. Scholars of world literature, postcolonial studies, and comparative literature alike will learn much from the innovative methodology he establishes in reading across different literary cultures and languages." -Neelam Srivastava, Professor of Postcolonial and World Literature, Newcastle University, UK This book links world-literary studies with anthropology and ethnography. It shows how ethnographic narratives can represent a compelling point of departure for world-literary explorations. The volume compares the travel writing and fiction of Robert Louis Stevenson and Rudyard Kipling as colonial ethnographic narratives; the militant writings of Carlo Levi and Mahasweta Devi; and the travelogues and ethnographic fiction of Amitav Ghosh and the literary journalism of Frank Westerman. Each of these readings focuses on a set of social, political and historical circumstances and relies on a dialogue with anthropological theory and history. This book demonstrates how imperialism, colonialism, capitalism and ecology are interdependent, and contributes to methodological debates within both anthropology and world-literary studies. Lucio De Capitani is Research Fellow in the Department of Linguistics and Comparative Cultural Studies at Ca' Foscari University of Venice, Italy. .
1. Ethnographic Fieldwork as a Point of Departure for World Literature -- 2. Colonial Ethnography and Uneven Intimacies in Robert Louis Stevenson and Rudyard Kipling -- 3. Militant Ethnography and Internal Colonialism in Carlo Levi and Mahasweta Devi -- 4. Patchy Ethnographies of Neocolonial and Neoliberal Landscapes in Amitav Ghosh and Frank Westerman -- 5. Conclusion.
Keywords: Literature; Ethnology; European literature; Oriental literature; Comparative literature; World Literature; Ethnography; European Literature; Asian Literature; Comparative Literature